Genetic Factors of Human Milk and the Genomic Interaction Between Mother and Infant: Faktor Genetik pada ASI dan Interaksi Genomik antara Ibu dan Bayi - Alyaa Abdulamir Attia (Academia Open, 2026)
General Background: Human milk is a complex biological system composed of nutrients, immune components, and regulatory molecules essential for infant development. Specific Background: Recent advances in genomic technologies, including RNA sequencing, genome-wide association studies, and multi-omics approaches, have enabled deeper investigation into the molecular composition of human milk. Knowledge Gap: Despite these advancements, the mechanisms underlying genetic regulation of milk composition and the bidirectional genomic interaction between mother and infant remain insufficiently understood. Aims: This study aims to analyze genetic factors influencing human milk composition and examine maternal–infant genomic interaction through a systematic review of studies published between 2019 and 2025. Results: The findings indicate that milk components such as proteins, lipids, oligosaccharides, miRNAs, and cell-free DNA are regulated by specific genes, including LALBA, FUT2, CSN2, LCN2, and BTN1A1, and are influenced by hormonal, immunological, and environmental factors. Evidence also demonstrates dynamic molecular communication between mother and infant, affecting gene expression in both. Novelty: The study highlights human milk as a genetically adaptive system facilitating bidirectional genomic signaling. Implications: These insights support the development of personalized nutrition strategies, integration of multi-omics research, and application of artificial intelligence in understanding maternal–infant biological interactions. Keywords: Genetic Factors, Human Milk, Genomic Interaction, Breastfeeding, Molecular Regulation Key Findings Highlights Specific genes regulate variability in milk biochemical composition across individuals Molecular signals enable two-way biological communication between mother and infant Regulatory molecules contribute to immune and developmental programming mechanisms